2018
DOI: 10.1136/bmjopen-2018-022138
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of overdetection of breast cancer among women 70 years of age and older in the USA: a mixed-methods analysis

Abstract: ObjectivesCurrent research on the perceptions of overdiagnosis or overdetection of breast cancer has largely been conducted outside of the USA and with women younger than 70 years.Therefore, we explored older women’s perceptions about the concept of overdetection of breast cancer and its influence on future screening intentions.DesignMixed-methods analysis using purposive sampling based on race/ethnicity, age and educational level. Semistructured interviews, including two hypothetical scenarios illustrating be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 31 publications
6
50
0
Order By: Relevance
“…Evidence shows that there is poor lay understanding of these concepts in the context of cancer screening and descriptions such as ''unnecessary diagnosis'' or ''diagnosis of a condition that would never have caused harm'' may be a better method to explain overdiagnosis. 37,49 Avoiding the use of the specific terms ''overdiagnosis'' and ''overtreatment'' may be purposeful. By describing these concepts rather than using the specific terms, PDA developers may be able to create aids with plain language communication and designed for the cultural context that may assist patients as they work to understand concepts related to overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows that there is poor lay understanding of these concepts in the context of cancer screening and descriptions such as ''unnecessary diagnosis'' or ''diagnosis of a condition that would never have caused harm'' may be a better method to explain overdiagnosis. 37,49 Avoiding the use of the specific terms ''overdiagnosis'' and ''overtreatment'' may be purposeful. By describing these concepts rather than using the specific terms, PDA developers may be able to create aids with plain language communication and designed for the cultural context that may assist patients as they work to understand concepts related to overdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Qualitative studies have assessed women’s views on overdetection, showing that women are often surprised or even upset when they hear about it. 9,10 Studies that assessed acceptance of overdiagnosis quantitatively have shown widely varying ratios, for example, from 50% accepting at maximum a 1:1 ratio when starting screening, to 60% of previous screeners accepting a 1:10 ratio. 11 Van den Bruel et al 12 added a limited description of the consequences of overdetection in terms of treatments that patients would undergo following diagnosis.…”
mentioning
confidence: 99%
“…In a separate analysis of these participants, Hoover and colleagues found that older women wanted the opportunity to hear about the benefits and harms of breast cancer screening from their physician or another health care provider . Additionally, Pappadis et al found that older women demonstrated a limited understanding of the downsides associated with continued screening, like overdiagnosis Our findings build on this prior work and highlight the role of physicians in screening decision making. Even though women intended to continue screening, they were willing to discuss breast cancer screening discontinuation in the 2 doctor's recommendation scenarios.…”
Section: Discussionmentioning
confidence: 99%